Primary School Teacher Education Students' Perceptions of the Use of ChatGPT in Language and Literature Teaching - Irvan Syahrizal; Fery Muhamad Firdaus (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
The rapid emergence of ChatGPT has generated significant attention in the education sector, particularly regarding its potential to support language and literature learning. This study investigates Primary School Teacher Education (PGSD) students’ perceptions of ChatGPT use in Indonesian Language and Literature courses. Employing a quantitative research design, data were collected from 333 undergraduate students across six Indonesian universities using a questionnaire adapted from Chellappa and Luximon. The instrument measured three perceptual dimensions: optimism, usefulness, enthusiasm and appreciation. Data were analyzed using descriptive statistics, one-sample t-tests, and MANOVA. The findings indicate that students generally hold positive perceptions of ChatGPT across all measured dimensions. One-sample t-test results show that mean scores for all items were significantly above the neutral benchmark, suggesting favorable student attitudes toward the technology. MANOVA results reveal no significant differences in perceptions based on gender or semester level. However, significant differences were found across universities, highlighting the influence of institutional context on technology acceptance. The results align with the Technology Acceptance Model and Self-Determination Theory, indicating that both cognitive evaluations and motivational factors contribute to students’ positive responses. Overall, ChatGPT demonstrates strong potential as a supportive cognitive and motivational tool in Indonesian Language and Literature learning. The study underscores the importance of institutional support and strategic integration to maximize the educational benefits of generative AI in teacher education contexts.